A New Azide-Bridged Polymeric Manganese (III) Schiff Base Complex with an Allylamine-Derived Ligand: Structural Characterization and Activity Spectra - Talebi, Aynaz; Salehi, Mehdi; Jesus, A. J. Lopes; Kubicki, Maciej; FAUSTO, RUI; Golbedaghi, Reza (MDPI, 2024)
This paper reports the synthesis and structural characterization of a novel azide-bridged polymeric manganese (III) Schiff base complex, using 2-((allylimino)methyl)-6-ethoxyphenol as a ligand. The crystal structure of the synthesized compound, elucidated by single-crystal X-ray diffraction analysis, indicates that it crystallizes in the monoclinic space group P21/c. The complex is found to display an octahedral geometry in which the central manganese Mn(III) coordinates with two bidentate donor Schiff base ligands via oxygen and nitrogen atoms. In addition, the metallic centers are linked together to form a one-dimensional chain bridged by end-to-end azide ligands. To offer a more thorough characterization of the synthesized compound, the study incorporates experimental data from FT-IR, UV-Vis, and cyclic voltammetry, alongside computational results from Hirshfeld surface analysis and DFT calculations conducted for both the ligand and complex. The computational analyses provided valuable insights into the intrachain and interchain interactions within the crystal structure, clarified the conformational characteristics of the isolated ligand molecule, and aided in the interpretation of the experimental IR spectra. Furthermore, an assessment of the compound’s drug-like properties was conducted using activity spectra for substances (PASS) predictions, revealing potential pharmacological activities. © 2024 by the authors.
Keywords: Activity Spectra; Crystal Structure; DFT Calculations; Hirshfeld Surface Analysis; Intermolecular Interactions; Schiff Base Complex; Spectroscopy